The Perpetuation of Regime Security in Gulf Cooperation Council States: A Multi‐Lens Approach. (15th March 2017) - Evren Tok, M.; McSparren, Jason J.; Olender, Michael
Abstract: Gulf Cooperation Council (GCC) states have been engaging in diversification efforts, yet the types of efforts suggest that the primary interest is regime security. Regional foreign policy is complex; hence we propose a multi‐lens approach to analyze overlapping and complementary political, economic, and social forces. The international political economy of hydrocarbons demonstrates the similarities among GCC states, regional dynamics illustrate interstate relations and similar patterns, while economic diversification suggests individual state trajectories and comparative and competitive patterns. By outlining the contemporary context for GCC states, we argue that low oil prices, regional dependence on hydrocarbons, and trends in economic diversification efforts signal GCC states' preference to reinforce their rentier systems with alternative state revenue streams. GCC states' diversification into new markets and sectors and use of state‐owned enterprises in microcompetitions indicate a new search for alternative revenue streams and prestige, which in turn are used to assure the perpetuation of regime security. This finding sets trajectories and implications for the region, specifically economic stagnation and supplementary diversification processes.